Arthroscopic reconstruction of anterior cruciate ligament injury with and without anterolateral ligament reconstruction in patients with sports injury - Abdelghany Abdelsattar, Hossam; Elbana, Emad; Alaaeldin Abdelrahman , Mohamed; Abdelbaset Abdelsamad, Ayman (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The current study aimed to evaluate postoperative knee stability in cases with high grade pivot shift test treated with ACL reconstruction with ALL reconstruction versus cases treated with ACL reconstruction only. This prospective comparative randomized study involved 40 patients with unilateral single ligamentous ACL injuries exhibiting advanced pivot shift test results. Patients were classified equally into two cohorts: Group I received solo ACL repair (ACLR), whereas Group II got ACL reconstruction with ALL reconstruction (ALLR). The postoperative scores from the International Knee Documentation Committee, Cincinnati, Lysholm, and Tegner were considerably elevated in the ACLR + ALLR group compared to the ACLR group (p<0.05), with notable improvements seen in both groups (p<0.05). The negative post-operative Lachman and Pivot shift tests were substantially greater in the ACLR + ALLR group than the ACLR group (p<0.05), and there was a high improvement pre- and post-operatively in the ACLR + ALLR group (p<0.05). The anterior drawer test demonstrated a substantial enhancement in both groups (P<0.05). Post-operative effusion exhibited a wide variation between groups (p<0.05), and there was a notable improvement in both groups (p<0.05). Post-operative pain was considerably reduced in the ACLR + ALLR group compared to the ACLR group (p<0.05), with notable improvement seen in both groups (p<0.05). The single leg hop test showed considerable improvement in both groups (p<0.05). Postoperative patient satisfaction exhibited a statistical variation between groups (p<0.05). Additional rotational stability is achieved through ACL + ALLR reconstruction, which enhances the likelihood of professional athletes returning to sports activities.